2022
DOI: 10.7554/elife.76576
|View full text |Cite
|
Sign up to set email alerts
|

SNTA1 gene rescues ion channel function and is antiarrhythmic in cardiomyocytes derived from induced pluripotent stem cells from muscular dystrophy patients

Abstract: Background:Patients with cardiomyopathy of Duchenne Muscular Dystrophy (DMD) are at risk of developing life-threatening arrhythmias, but the mechanisms are unknown. We aimed to determine the role of ion channels controlling cardiac excitability in the mechanisms of arrhythmias in DMD patients.Methods:To test whether dystrophin mutations lead to defective cardiac NaV1.5–Kir2.1 channelosomes and arrhythmias, we generated iPSC-CMs from two hemizygous DMD males, a heterozygous female, and two unrelated control mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…In addition, whereas the barium‐sensitive component seemed to contribute only in part to the outward current in WT cells, DYS myocyte outward currents were almost barium‐insensitive. In cardiomyocytes, a similar reduction of this Kir‐mediated attribute has been observed in mdx ventricular cardiomyocytes 19 and in iPSC‐cardiomyocytes from DMD patients 62 …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, whereas the barium‐sensitive component seemed to contribute only in part to the outward current in WT cells, DYS myocyte outward currents were almost barium‐insensitive. In cardiomyocytes, a similar reduction of this Kir‐mediated attribute has been observed in mdx ventricular cardiomyocytes 19 and in iPSC‐cardiomyocytes from DMD patients 62 …”
Section: Discussionsupporting
confidence: 65%
“…In cardiomyocytes, a similar reduction of this Kir-mediated attribute has been observed in mdx ventricular cardiomyocytes 19 and in iPSC-cardiomyocytes from DMD patients. 62 The lower expression of Kcnj2 is also in agreement with reduced Myog mRNA level in DYS myocytes; this again corroborates that terminal differentiation may be altered in DYS cells. Of note, Kcnj2…”
Section: Inward and Outward Currentssupporting
confidence: 69%
“…We are considering the possibility of alterations in other ion channel properties because of dystrophin deficiency. In fact, downregulation of voltage‐sensitive sodium channels was reported in cardiomyocytes derived from induced pluripotent stem cells from muscular dystrophy patients (Jienez‐Vazquez et al, 2022). If the similar changes happened to DS‐type neurons in D m rats, it might be reasonable that no significant change was observed in action potential waveforms between WT and D m rats (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned variants may impair membrane trafficking, modify channel gating properties or kinetics, or cause haploinsufficiency due to premature transcriptional stop signals. Specifically, previous research has revealed a decrease in I Na and I K1 density and conduction www.cardiologyplus.org Huang K and Ren J: Cardiology Plus velocities or a loss of regulation by intracellular factors in signal transduction, including protein kinase A (PKA), ankyrin G, or a1-syntrophin [20][21] .…”
Section: Genetic Findings Of Brugada Syndromementioning
confidence: 99%